What is the Better Social Media for Mathematics Learning? A Case Study at A Rural School in Yogyakarta, Indonesia - Sulisworo, Dwi; Permprayoon, Kasem (International Journal on Emerging Mathematics Education, 2018)
The penetration of social media in the community has been very high. Nowadays, almost all students at the school are using smartphones for their daily activities. This study is a descriptive quantitative exploratory research to find out how the students response when learning using social media is implemented as a mobile learning system. Data were taken from four different schools in the rural area of Yogyakarta, Indonesia. Mathematics learning using a different social media (WeChat, Line@, Socrative, and Edmodo) was applied to student of grade 7 of each school. Data collection used USE questionnaire which measured whether the implemented learning model using social media could be well received by students and appropriate learning expectations. USE questionnaire has 4 measured factors i.e. usefulness, ease to use, ease of learning, and satisfaction. From the data, it shows that all factors were high. The highest one was satisfaction (3.15) then, usefulness (3.11), ease to learn (3.00), and ease to use (2.94) respectively. On average, the social media got the highest studentâs response as a learning system was Socrative (3.18), then Edmodo (3.15), Line@ (3.00) and WeChat (2.89). Further analysis using statistical technique showed that students have good perception to Socrative and Edmodo. This finding implies that the social media especially Socrative and Edmodo are valuable to be used in the leaning using flexible learning strategy.